RECENT DEVELOPMENT OF POTENTIAL THERAPY FROM NATURAL COMPOUNDS IN Helicobacter pylori INFECTION: A SYSTEMATIC REVIEW - Susanti; Afifudin, Alfin Fatwa M. (Jurnal Biosains Pascasarjana, 2025)
This work performs a systematic literature review on potential Natural Product in Helicobacter pylori (H. pylori) and discusses the development of potential therapy from various natural resources. A search method was used to locate papers published between 2019 and 2024 in Web of Science and PubMed databases, and 14 studies were selected. Reports on potential Natural Product in H. pylori, in vitro and in vivo study design are included. Articles not written in English or whose full text could not be accessed were excluded. The remaining publications were checked and evaluated to determine whether they contain supportive natural product in H. pylori infection. The majority of articles are used non RCT study design and Minimum Inhibitory Concentration (MIC) was the most commonly utilized parameter in these studies. These studies generally focus on in vitro investigation using natural product such as licorice root extract, C. striata extract, propolis extract, and virgin olive oil extract on the certain strains of H. pylori. Different extracts of natural products were reported to have different particular effects on H. pylori including antimicrobial activity, the regulation of inflammatory cytokines and genes, and the association of protection and histopathology effects.There has been numerous research on potential Natural Product in H. pylori infection, but it is not yet applicable in health practice. In the future, the potential Natural Product studies expected to reach the clinical study stage and to contribute to the invention on the treatment of H. pylori infection.